Relation of CRP Level with the Severity of Coronary Artery Stenosis in Diabetic Patients: CRP Level and the severity of Coronary artery stenosis - Nough, Hosein (Journal of Cardiology and Cardiovascular Medicine, 2025)
Background: Atherosclerosis is a disease characterized by the deposition of lipids on the inner walls of blood vessels. Diabetes is a significant risk factor for atherosclerosis. C-reactive protein (CRP) is a marker of systemic inflammation and an independent risk factor for cardiovascular diseases (CVD). This study aimed to investigate the relationship between serum CRP levels and the severity of coronary artery disease in diabetic patients. Materials and Methods: This descriptive-analytical study was conducted on 185 diabetic patients referred for coronary angiography based on non-invasive test indications. A checklist based on demographic information, blood pressure, and duration of diabetes was completed, and CRP testing was performed for each patient. Coronary angiographic data were also collected, including the type and severity of involved vessels reported by two cardiologists. Results: There was a significant relationship between serum CRP level and the severity of coronary artery disease (P-value=0.009). Additionally, there was a significant relationship between the duration of diabetes and the severity of coronary artery disease (P-value=0.006). Conclusion: We found a significant relationship between serum CRP levels and the severity of coronary artery stenosis and between the duration of diabetes and the severity of coronary artery stenosis.